2014
DOI: 10.1007/s00415-014-7454-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating shunt-responsive normal pressure hydrocephalus from Alzheimer disease and normal aging: pilot study using automated MRI brain tissue segmentation

Abstract: Evidence suggests that normal pressure hydrocephalus (NPH) is underdiagnosed in day to day radiologic practice, and differentiating NPH from cerebral atrophy due to other neurodegenerative diseases and normal aging remains a challenge. To better characterize NPH, we test the hypothesis that a prediction model based on automated MRI brain tissue segmentation can help differentiate shunt-responsive NPH patients from cerebral atrophy due to Alzheimer disease (AD) and normal aging. Brain segmentation into gray and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…Patients with hydrocephalus generally show clinical symptoms, ventriculomegaly and anomalous cerebrospinal fluid (CSF) dynamics [1,2]. Normal pressure hydrocephalus (NPH) can appear as a primary condition [3] or as a consequence of subarachnoid haemorrhage, traumatic brain injury (TBI) or meningitis [1,3]. Implantation of a CSF shunt is the main treatment option [4].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with hydrocephalus generally show clinical symptoms, ventriculomegaly and anomalous cerebrospinal fluid (CSF) dynamics [1,2]. Normal pressure hydrocephalus (NPH) can appear as a primary condition [3] or as a consequence of subarachnoid haemorrhage, traumatic brain injury (TBI) or meningitis [1,3]. Implantation of a CSF shunt is the main treatment option [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the identification of patients with NPH most likely to benefit from shunting procedures remains difficult. 8,17,21 Marmarou et al performed a literature review and found that the sensitivity of predicting successful outcomes based on clinical and imaging findings alone can be as low as 46%. The addition of high-volume lumbar puncture (HVLP) yielded a sensitivity of 26%-61%, and CSF outflow resistance studies had sensitivities of 57%-100%.…”
mentioning
confidence: 99%
“…3 The diagnosis of NPH is characterized by several neuroimaging features, including ventricular dilation in the presence of normal gray matter volume, but despite a very large number of publications since 1964, the role of neuroimaging in predicting the response to shunting remains uncertain. 4,5 Tarnaris et al 6 performed a literature review of 69 studies published between 1980 and 2006 to examine the role of structural as well as functional imaging in providing biomarkers of favorable surgical outcome in NPH. The papers reviewed included studies of structural CT and MR imaging features; 4,6-9 phase-contrast MR imaging studies of aqueductal CSF velocity and stroke volumes; [10][11][12] and functional studies including xenon-enhanced CT, 13 FDG-PET, 14,15 singlephoton emission CT, 16 and MR imaging spectroscopy.…”
mentioning
confidence: 99%